2012
DOI: 10.2478/s11534-011-0100-x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the LO phonon energy by using electronic and optical methods in AlGaN/GaN

Abstract: Abstract:The longitudinal optical (LO) phonon energy in AlGaN/GaN heterostructures is determined from temperature-dependent Hall effect measurements and also from Infrared (IR) spectroscopy and Raman spectroscopy. The Hall effect measurements on AlGaN/GaN heterostructures grown by MOCVD have been carried out as a function of temperature in the range 1.8-275 K at a fixed magnetic field. The IR and Raman spectroscopy measurements have been carried out at room temperature. The experimental data for the temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…6(b). Although the calculated power loss does not offer a satisfactory fit to the experimental data in the electron temperature range between 20 and 150 K, it fits reasonably well to the experimental data for T e > 150 K. From the temperature dependence of the Hall mobility compared with the calculated various electron mobility was shown that the mobility of electrons in Al 0.25 Ga 0.75 N/AlN/GaN heterostructures is determined by mixed interface roughness scattering and polar optical phonon scattering in the temperature range between 20 and 150 K [21]. Therefore, it is clear that the addition of the other scattering time together with the optical phonon scattering time is necessary in the definition of the electron-phonon scattering time (Eq.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…6(b). Although the calculated power loss does not offer a satisfactory fit to the experimental data in the electron temperature range between 20 and 150 K, it fits reasonably well to the experimental data for T e > 150 K. From the temperature dependence of the Hall mobility compared with the calculated various electron mobility was shown that the mobility of electrons in Al 0.25 Ga 0.75 N/AlN/GaN heterostructures is determined by mixed interface roughness scattering and polar optical phonon scattering in the temperature range between 20 and 150 K [21]. Therefore, it is clear that the addition of the other scattering time together with the optical phonon scattering time is necessary in the definition of the electron-phonon scattering time (Eq.…”
supporting
confidence: 74%
“…1). This behavior reflects the 2D character of the electrons in the channel [19][20][21]. It is also evident that the oscillatory effect is superimposed on a monotonically increasing component, which occurs as a result of positive magnetoresistance in the barriers [7,19].…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…One of the most important parameter in the rate equations is the inter-level electron relaxation lifetime. In this paper, we calculated the inter-level electron relaxation lifetime due to the different scattering mechanisms [5,19,20]. We found it in order of 1 ps, for example, 0.21 ps at T = 300 K, and 0.46 ps at T = 250 K.…”
Section: Theoretical Modelmentioning
confidence: 96%
“…1 This regime occurs when electrons travel a distance shorter than their mean free path l m (average distance between consecutive scattering events), which can be as small as tens of nanometers depending on the material. Therefore, ballistic transport is a nanoscale phenomenon, requiring nanoscale structures.…”
Section: Magneto-ballistic Transport In Gan Nanowiresmentioning
confidence: 99%